MANAGEMENT ANALYSIS OF SCHOOL RELATIONSHIP WITH COMMUNITIES IN SDN MANGGARAI 05 SOUTH JAKARTA - Ritonga, Rudi (International Journal of Educational Management and Innovation, 2020)
Educational institutions must be supported jointly by all parties, both families, schools, and communities. This third component must work together in harmony so that it can produce quality educational outcomes. Untul, the school is expected to improve relations with the family or guardians of students, and the community, in general, to work together in realizing the management of school relationships with good community management. This study aims to describe how to manage school relations with the community, also to find out what is in SDN Manggarai 05, South Jakarta. This type of research is qualitative research, while the form is field research, by taking location at SDN Manggarai 05 South Jakarta. Data collection methods used are, observation, interview and documentation. Whereas the process of data analysis used Miles and Huberman model analysis, namely interactive model analysis with steps: data collection, data reduction, data display, data verification and data interpretation. The results of this study are in accordance with the Public Relations indicators show; first, related to educational relationships formed by the formation of schools. However, meetings or meetings are conducted at the time of report cards, so it is not yet at an intensive stage. This results in the absence of effective planning, implementation and evaluation. Second, the cooperative relationship between SDN Manggarai 05 and institutions such as Puskesmas, Kelurahan, Kecamatan, Polsek, BNN and Universities has been established. However, it has not been fully done. Third, what is the challenges in public relations management are known by two factors, namely internal factors, and external factors. The first is internal factors, which are known to have no special personnel given regarding the relationship between SDN Manggarai 05 and the community. While the external factor is known as the guardian, the students give up the children's education process at school.